2014
DOI: 10.1038/srep06457
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic control of axonal guidance

Abstract: The precision of axonal pathfinding and the accurate formation of functional neural circuitry are crucial for an organism during development as well as during adult central and peripheral nerve regeneration. While chemical cues are believed to be primarily responsible for axonal pathfinding, we hypothesize that forces due to localized fluid flow may directly affect neuronal guidance during early organ development. Here, we report direct evidence of fluid flow influencing axonal migration, producing turning ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Copyright 2014 MacMillan Publishers. (D) Adapted with permission from ref ( 216 ). Copyright 2015 Nature Publishing Group.…”
Section: Hydrodynamic Effects On Cells On Standard Open Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2014 MacMillan Publishers. (D) Adapted with permission from ref ( 216 ). Copyright 2015 Nature Publishing Group.…”
Section: Hydrodynamic Effects On Cells On Standard Open Substratesmentioning
confidence: 99%
“…For example, open-space hydrodynamic devices have also been used to exert mechanical (shear) forces on selected cells in an open and immersed environment. Gu et al 216 assessed the impact of fluid flow on axonal migration, producing turning angles of up to 90° by applying flows. Microfluidic flow simulations indicated that an axon may experience significant bending forces due to cross-flow, which are likely to contribute to the observed axonal bending.…”
Section: Hydrodynamic Effects On Cells On Standard Open Substratesmentioning
confidence: 99%
“…Physical cues are in general electrical 2 and optical 3 ) in nature or any combination thereof. Focused laser beam has enabled modulation and generation of several chemical 4 5 and physical (force 3 6 and fluid flow 7 8 9 ) cues to influence axonal guidance. In general, the light-based methods for axonal guidance can be divided into two categories, indirect and direct.…”
mentioning
confidence: 99%
“…Second, it combines both geometrical and AC field growth constraints to control the connections between the nodes, allowing constraint-free positioning of nodes relatively to each other. Compared to existing neurite guidance techniques, either by controlling adhesive cues 33 34 35 or using microfluidic grooves 36 or both 37 or other techniques 38 39 , our method allows a dynamic multiplexed manipulation of neurites within the same groove, which enables the precise relative positioning of several neurites at the same time. Using our technique, in-vitro neural networks would not be limited by their structural connectivity between nodes, allowing the creation of complex networks with more than three nodes.…”
Section: Resultsmentioning
confidence: 99%